PVD synthesis of binder-free silicon and carbon coated 3D α-Fe2O3 nanorods hybrid films as high-capacity and long-life anode for flexible lithium-ion batteries. (1st December 2018) - Wang, Mingyue; Huang, Ying; Wang, Ke; Zhu, Yade; Zhang, Na; Zhang, Hongming; Li, Suping; Feng, Zhenhe
Abstract: Flexible lithium-ion batteries are being given great attention as up-and-coming power source for the development of flexible and wearable electronic devices. In this work, a carbon and silicon coated 3D α-Fe2 O3 nanorod arrays on carbon cloth composite was firstly designed by facile hydrothermal method and physical vapor deposition process. The as-prepared composite can be directly applied as flexible anode for Li-ion batteries without adding any binder and conducting materials. The electrochemical results show that the composite exhibits outstanding electrochemical lithium storage properties with high initial Coulombic Efficiency of 76% at 100 mA g −1 current density and a superior cycling performance that could maintain about 910 mAh·g −1 after 500 cycles at a 500 mA g −1 current density, which is two to three times of commercial graphite anodes. This study offers a promising route to greatly enhance the electrochemical properties of metal oxides and provides suggestive insights for developing high-performance electrode materials for flexible energy storage devices. Highlights: Binder-free α-Fe2 O3 @Si@C/carbon cloth flexible electrode was prepared via a facile route. α-Fe2 O3 @Si@C/carbon cloth electrode is composed of carbon cloth, α-Fe2 O3 nanorods, silicon and carbon coating layer. α-Fe2 O3 @Si@C/carbon cloth anode exhibits high specific capacity and stable cycling performance. α-Fe2 O3 @Si@C/carbon cloth anode displays good rate-capability and flexibility.